Place attachment and continuity of urban place identity - Ujang, Norsidah (Faculty of Architecture, Planning and Surveying, Universiti Teknologi MARA, 2010)
This paper focused on place attachment and its significance in defining place identity with reference to three main shopping streets in the city centre of Kuala Lumpur, Malaysia. Place identity refers to the identification of emotion and feelings to a particular place and the distinctive characteristics of the place in which human-place bonding is developed. The weakening of place identity has been identified as one of the urban design issues for contemporary cities. This paper identified the issues concerning place identity; concepts of place and place attachment constructs, the identification of place attachment constructs and place attributes that could be used as assessment indicators for future redevelopment of local urban places. A questionnaire survey and interviews were conducted to examine place attachment and to identify the characteristics of the places that exerted influence and would then benefit in terms of securing place identity which in turn sustained attraction and thus brought greater economic and tourism advantages to the city.